1991
DOI: 10.1111/j.1365-2621.1991.tb05291.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Quality Characteristics of Chymosin Extracts Obtained by Ultrasound Treatment

Abstract: An ultrasound method was developed for increased efficiency of chymosin extraction. Ultrasound extraction was carried out with a Tekmar sonic disrupter, and control extraction was by shaking. Use of ultrasound resulted in increase in activity and decrease in nitrogen content, thus increasing the specific activity of chymosin extracts. Proteolytic activity of experimental chymosin was higher at 15 and 20°C, but lower at 35 and 40°C than that of controls. Chymosin extracts obtained by ultrasound treatment were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 11 publications
1
3
0
Order By: Relevance
“…The data from Table 1 showed a significant decrease in proteolytic activity (PA) for the UP80 treatments 0.62 ±0.07 than that in the traditional control treatment 0.95 ±0.05 µg tyrosine/min./ml. This finding is in agreement with Kim & Zayas, (1991) who reported that the chymosin treated by ultrasound might lost proteolytic activity as the ultrasound exposure time increased more easily than that extracted by the traditional method. The rennet with excessive PA enzymes is not used in cheese-making due to the higher proteolytic activity in the cheese.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…The data from Table 1 showed a significant decrease in proteolytic activity (PA) for the UP80 treatments 0.62 ±0.07 than that in the traditional control treatment 0.95 ±0.05 µg tyrosine/min./ml. This finding is in agreement with Kim & Zayas, (1991) who reported that the chymosin treated by ultrasound might lost proteolytic activity as the ultrasound exposure time increased more easily than that extracted by the traditional method. The rennet with excessive PA enzymes is not used in cheese-making due to the higher proteolytic activity in the cheese.…”
Section: Resultssupporting
confidence: 92%
“…Zayas, (1986) noted that the duration of ultrasonic time was correlated with the concentration of chymosin and the highest yield and activity of chymosin enzyme were achieved after 60 min of ultrasonic exposure time. Similarly, (Kim & Zayas, 1991) reported that the ultrasound treatments destroyed the cellular structure through cavitation effects, which caused enhancement in the penetration and increment the permeability and accelerated releasing chymosin enzymes from cells to the medium. It appeared that the ultrasound exposure time treatment at 80 min with abomasum powder (UP80) had significantly higher effectiveness to camel chymosin extraction than the ultrasound exposure time 80 with strips form abomasum (US80) and the control treatment.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…1960). Kim and Zayas (1991) introduced an ultrasound‐assisted procedure for abomasal tissue extraction; chymosin activity in such extracts was higher than in conventional extracts, and no effects on proteolytic activity nor on storage stability were observed. After optimising ultrasound extraction of kid abomasa Zhang and Wang (2007) observed a significantly faster enzyme transfer and increased enzyme yield.…”
Section: Chemistry and Production Technologymentioning
confidence: 99%